COMPARISON OF TWO METHODS FOR RECORDING FROG’S MYOCARDIOGRAM - Farooq, Yasir; Hussain, Muhammad Mazhar; Furqan, Muhammad; Khan, Muhammad Alamgir; Yousaf, Iftikhar (Pakistan Journal of Physiology, 2007)
Background: Frog’s myocardiogram gives the medical students a clear understanding of the normal sequence of atrial and ventricular contraction and the effect of temperature, sympathetic stimulation and parasympathetic stimulation on frog’s heart. The purpose of this study was to compare two methods used for recording of frogs myocardiogram, namely kymographic method and iWorx data acquisition unit Method, keeping in view the difference between the recordings obtained by two methods and the convenience for the medical students in recording the myocardiogram by the two methods. Method: Frog was dissected and myocardiogram recorded first with the kymograph and than with the iWorx data acquisition unit. Frog’s saline was pored at regular intervals and both kymographic and iWorx readings were taken thrice at an interval of 5 min. Results: In the myocardiogram height of the recording on the y-axis indicates the strength of contraction by the frog heart. The height of myocardiogram recorded on the kymographic recording at intervals of 5 min each was compared with the height of the myocardiogram recorded on iWorx data acquisition unit at the same time. Comparison of the results at the same time interval show that iWorx data acquisition unit system reflects the mechanical activity of heart better than the conventional kymographic method. Even when the kymograph show no record of myocardial contractility the iWorx data acquisition unit still show the activity of the myocardium. Conclusion: This study shows that iWorx system reflects the mechanical activity in myocardium even when the kymograph cannot record it.